Nursing performance in infections associated with the installation of a central venous catheter in an intensive care unit (Research, Society and Development, 2023)
Objectives: the general objective of this research project is to analyze scientific evidence in the literature regarding the role of nursing professionals in preventing infections associated with the installation of a central venous catheter. Having as specific objectives, i) Clarify pre-existing protocols on insertion of central venou catheter; ii) survey of definitions of what bloodstream infections are iii) analyze the qualification of the nursing team in CVC care. Method: Integrative literature review, in the Nursing Database (BDENF), Latin American and Caribbean Literature in Life Sciences Saúde (LILACS) and Medical Literature Review and Online Recovery System (MEDLINE), analyzed the publications by year, language, type of production, abstract and title. The final sample consisted of 10 selected articles. Results: the study pointed out that the main precautions for prevention are hand hygiene, using the maximum barrier for catheter insertion.